The Cost Accounting and Finance Management Analysis Young Coconut Waste Business - Sari, Nur Zeina Maya; Rosimah, Siti; Rohmana, Rohmana; Larasati, Putri Dinda; Faisal, Rafi Ahmad (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
This research to find out about cost accounting and financial management of coconut shell waste produced in Bandung. Cost Accounting can be seen from the decrease in variable cost of young coconut waste. Then Financial Management for young coconut entrepreneurs by planning Break event point , Internal Rate of return and Benefit cost ratio. The lack of cost accounting records is an obstacle for coconut traders. Without proper planning, young coconut waste. Young coconut waste actually has high cost accounting and finance management it further processed with a touch of technology and the creativity and innovation of humans who care about this. Many research and community service activities have utilized young coconut waste into various products that have high value. The cost accounting and finance management of young coconut waste based on literature studies and empirical studies of young coconut business people as well as the design of a machine for chopping young coconut waste to become a new product that has added value. The method used is descriptive quantitative research with a case study of young coconut traders in the Gelora Bandung Lautan Api (GBLA). The results of the feasibility analysis with technical aspects using a machine for chopping young coconuts into cocopeat and coco obtained a, Cost Accounting: internal rate of return (RR) = 21 % and yield point (BEP) = 27,373 kg of coco, with finance management benefit cost ratio (BCR) = 2.05 achieved in the first year. The research position was carried out in Bandung after the FGD (forum group discussion) process. The benefit is to find out the influence of cost accounting and financial management on coconut shell waste. Answering the problems of MSME actors in cost accounting, young coconut financial management and knowledge development.